The acceptance of conditionally automated cars from the perspective of different road user groups - Schrauth, Bernhard; Funk, Walter; Maier, Sarah; Kraetsch, Clemens (European Journal of Transport and Infrastructure Research, 2021)
The foreseeable advent of conditionally automated cars (CACs) at SAE Level 3 opens a range of opportunities along with numerous questions that must be addressed to safely adopt this new vehicle technology. While public acceptance and the acceptance of potential users have already been intensively researched, this study investigates the acceptance of CACs from the point of view of different road user groups, such as pedestrians, cyclists and riders of powered two-wheelers (PTWs) as so-called vulnerable road users (VRUs), as well as the drivers of conventional cars. The study measures a priori road user acceptance of CACs using an international population survey that was conducted within the framework of the EU-funded project ‘BRidging gaps for the adoption of Automated Vehicles’ (BRAVE) in the participating countries France, Germany, Slovenia, Spain and Sweden as well as in Australia and the USA. Including 5,827 respondents, the study findings disclose a rather positive acceptance of CACs from the perspective of different road user groups. However, concerns are also apparent. Results from multivariate analyses indicate that the acceptance of CACs differs between road user groups in that VRUs demonstrated lower acceptance than non-automated car drivers. The role of trust in the new vehicle technology also appears to be remarkable. Consequently, future developments of CACs should also focus on communication between automated cars and bystanders (e.g. via external human-machine interfaces) to reduce uncertainties and promote trust.